2015
DOI: 10.5505/cayb.2015.32042
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of neurologic patients who treated therapeutic plasmapheresis at pediatric intensive care unit: 10 years experience

Abstract: Methods:Results: --2015;2(3):111-4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Treatment should be initiated as soon as the patient is diagnosed. Plasmapheresis treatment improves motor nerve healing and decreases mechanical ventilator support duration …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment should be initiated as soon as the patient is diagnosed. Plasmapheresis treatment improves motor nerve healing and decreases mechanical ventilator support duration …”
Section: Discussionmentioning
confidence: 99%
“…Plasmapheresis treatment improves motor nerve healing and decreases mechanical ventilator support duration. 36 ADEM is a neurologic disease affecting the white matter of brain and spinal cord and is caused by disseminated multifocal inflammation and demyelination secondary to autoimmune response. According to ASFA, TPE should be considered as a second line treatment in patients unresponsive to high-dose intravenous corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…According to the ASFA criteria, TPE is the first-line treatment (category I) in patients with neurological diseases such as GBS and anti-N-methyl-D-aspartate (NMDA) receptor encephalitis. 2,23 In a multicenter retrospective study with 49 153 patients, 25.6% of patients are diagnosed with neurological diseases and it is reported that the survival rate in patients treated with TPE was significantly higher, compared to the neurological patients not treated with TPE. 17 In our study, 9.8% of our patients were diagnosed with neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A girl with the diagnosis of systemic lupus erythematosus that underwent TPE for hemolytic anemia developed allergic reaction and thus was administered 5% albumin as a replacement fluid in the subsequent sessions. Tolunay et al [12], in a study whereby they assessed patients with neurological disorders undergoing plasmapheresis, reported that they most commonly encountered hypotension at a rate of 29.2%, followed by fever and allergic reactions with a rate of 9.7% and hypertension with a rate of 4.8%. We are of the opinion that making a correct indication, selection of a correct replacement fluid, and the team having experience in the procedure is equally effective in procedural success.…”
Section: Discussionmentioning
confidence: 99%